2015
DOI: 10.1093/humrep/dev139
|View full text |Cite
|
Sign up to set email alerts
|

How successful is TESE-ICSI in couples with non-obstructive azoospermia?

Abstract: None declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 25 publications
5
72
4
3
Order By: Relevance
“…Genetic causes of azoospermia include chromosomal abnormalities, Y chromosome microdeletions and specific mutations/deletions of several Y chromosomal genes (Miyamoto, Minase, Okabe, Ueda, & Sengoku, 2015). Approximately 10% of all male infertility cases (<1% of all men) are associated with non-obstructive azoospermia (Anniballo et al, 2000;Jarow, Espeland, & Lipshultz, 1989;Vloeberghs et al, 2015). This is a histopathological diagnosis based on testicular biopsy findings including hypospermatogenesis, maturation arrest [also called meiotic arrest (MA)] or Sertoli cell-only syndrome (SCOS).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic causes of azoospermia include chromosomal abnormalities, Y chromosome microdeletions and specific mutations/deletions of several Y chromosomal genes (Miyamoto, Minase, Okabe, Ueda, & Sengoku, 2015). Approximately 10% of all male infertility cases (<1% of all men) are associated with non-obstructive azoospermia (Anniballo et al, 2000;Jarow, Espeland, & Lipshultz, 1989;Vloeberghs et al, 2015). This is a histopathological diagnosis based on testicular biopsy findings including hypospermatogenesis, maturation arrest [also called meiotic arrest (MA)] or Sertoli cell-only syndrome (SCOS).…”
Section: Introductionmentioning
confidence: 99%
“…The median dosage of gonadotropins used was 1950 IU (interquartile range, 1650-2550 IU), duration of stimulation 12 days (11-14 days), peak oestradiol level 11 341 pmol/L (7859.5-19 260.5 pmol/L), and the number of metaphase II oocytes obtained was 8 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Pregnancy test was positive in 15/89 (16.9%) and the clinical pregnancy rate was 12/89 (13.5%).…”
Section: Resultsmentioning
confidence: 99%
“…17 With increasing awareness of male infertility, it is hoped that more men will seek professional help and share the burden in fertility treatment. Nevertheless, existing data available in the literature on outcomes of IVF-TESE are fragmentary 5 and local data are still lacking. Karyotypic abnormalities and Y-microdeletion have been associated with severe male factor infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, spermatozoa were obtained with m-TESE in 36% of the patients with nonobstructive azoospermia. [9] Vloeberghs et al [10] found sperm retrieval, and pregnancy rates related to TESE procedure as 40.5, and 37%, respectively. They determined that 13.4% of all patients who had undergone TESE had delivered healthy babies.…”
Section: Discussionmentioning
confidence: 98%